THE ROLE OF ENGLISH LITERACY IN ENHANCING STUDENTS’ READING AND WRITING SKILLS - Kusumastiti, Weka (Jurnal Review Pendidikan dan Pengajaran, 2025)
This study aims to examine the role of English literacy in improving students' reading and writing skills through a literature review approach. English literacy is understood as a complex process that involves not only the technical skills of reading and writing but also the comprehension of meaning, critical thinking, and the expression of ideas in written form. Through the exploration and analysis of various scholarly sources from accredited national journals, scientific articles, and academic publications, it is found that literacy significantly influences the development of students' language skills across different education levels. Key findings reveal that innovative methods such as gallery exhibitions, Jolly Phonics, digital platforms like Padlet, and project-based and storytelling approaches effectively enhance students' reading comprehension and writing skills simultaneously. Moreover, the role of teachers, the use of technology, and the integration of character values into literacy practices have proven to strengthen the effectiveness of English language learning. However, challenges remain, including low student motivation and weak foundational literacy, especially at the elementary level. This research highlights the need for an integrated, adaptive, and contextual literacy approach to create more effective and meaningful learning experiences. Therefore, English literacy serves not only as a tool for academic improvement but also as a means of holistic student development.